Discursive Articulation and Thirdspace Production in the Contestation of Residential Space along the Dupak Magersari Railway Line in Surabaya - Galang Geraldy; Dwi Windyastuti; Muhammad Asfar (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2026)
This study aims to analyse how residential space along the Dupak Magersari railway line in Surabaya is produced through a dialectical process of discursive articulation that shapes the negotiation of spatial meaning. Using the frameworks of discursive hegemony (Laclau & Mouffe), spatial production (Lefebvre), and Thirdspace (Soja), this study positions space not merely as a physical entity, but as a field of contestation over definitions, legitimation, and regimes of truth. This qualitative research with a case study approach utilises observation, in-depth interviews, and analysis of policy documents and media. Findings show that the dominant discourse of the state and corporations—which positions the railway border as an illegal, risky zone, devoid of residential function—is confronted by a counter-discourse that emphasises social legitimacy, sustainability of life, and the right to space. This contestation is mediated by formal local political actors, particularly the Regional Representative Council and the Surabaya City Government, which function as important nodes in discursive negotiations between the legal-administrative framework and citizens' demands for legitimacy. At the same time, the presence of communities, academics, and urban social networks expands the field of articulation, not as a centre of hegemony, but as a reality that enriches the discursive ecosystem of space. Through the formation of chains of equivalence, the discourse of "illegality" undergoes a dislocation of meaning and is contested by the narrative of "socially legitimate living space". This process produces a new nodal point that redefines the railway boundary not merely as an object of state control, but as a space whose meaning is negotiated. This contestation does not produce a final resolution between legal and illegal, but rather forms a Thirdspace—a hybrid space that lives in discursive tension and reconciliation. This study affirms that the dynamics of space at the railway boundary are a hegemonic battle over the meaning of space that transcends the technocratic framework of urban planning, and highlights the importance of discourse articulation in the production of contemporary urban space.